Analysis of the Influence of Technology, Infrastructure and the Democratic System on Unemployment in Indonesia - Arsyad, Rahmat; Anwar, Anas Iswanto; Lenas, Meldilianus Nabas J.; Bahasoan, Awal Nopriyanto (Perpustakaan dan Penerbitan Unismuh Makassar, 2023)
This study aims to analyze the effect of Technology, Infrastructure, and the Democratic System on Indonesia's unemployment from 2011-2021. The independent variables in this study are technology, infrastructure, and democratic systems, while the dependent variable is unemployment. This research is a correlational study with a quantitative approach. The data used in this study is secondary data obtained from the publication of the Central Bureau of Statistics (BPS). The research sample was taken by using the purposive sampling method. The data analysis method used is multiple linear regression analysis using the SPSS application. The research results show that technology and infrastructure variables significantly positively affect unemployment. Meanwhile, the democratic system variable has no significant effect on unemployment in Indonesia